The moon moth - Ibrahim, Humayoun (First Second, 2012)
"Edwer Thissell is having trouble adjusting to life on the planet Sirene. The Sirenese all wear masks to indicate their social status. They also communicate by playing instruments that are carefully selected for any social situation. (To make matters worse, errors of musical etiquette often prove fatal.) Shortly after Thissell arrives on Sirene, he finds himself embroiled in an unsolved murder made all the more mysterious by the fact that since everyone must always wear a mask, you can never be sure who you are dealing with ..."--P. [4] of cover.